Tehniški dnevi v prvem triletju devetletne osnovne šole - Rajšp, Martina; Žic, Jasna; Glavič, Sara (Revija za elementarno izobraževanje, 2008)
Technical Days in the First Three Years of Elementary School. In the article we define and present in detail the so called “Technical Days” in Slovenian elementary schools. We empirically evaluated the technical workbooks used in the first three years of elementary school. These workbooks were approved by the Technical Council of the Slovenian Common Education.We established that none of these books offer support to teachers who are organizing and evaluating Technical Days. The research consisted of first, second and third grade teachers fromMaribor elementary schools. The results of our research show that all the teachers who participated were familiar with how to carefully plan, execute and evaluate Technical Days.
Keywords: primary school; Days of Activity; Technical Days; first three years of the nine-year elementary school